Implementation of the E-Ticket System on Traffic Awareness - Fahas Bullah, Muhammad; Riky Novarizal, (Sisi Lain Realita, 2023)
Road traffic violations are acts or actions that violate the Traffic Law. Law enforcement activities for traffic violations were previously only subject to manual tickets (tickets). Realizing this, the Police of the Republic of Indonesia created an electronic-based innovation to take action against traffic violations based on Kaposri regulation No. 5 of 2012 concerning Registration and Identification of Motorized Vehicles. This update was made to provide several good options for the police to overcome problems that occur in traffic and to eliminate errors in the use of power for individual interests, collusion, corruption and nepotism (KKN) in old traffic tickets. E-Tilang is also an update used by the police because there were many violations in the 2018-2023 period. With traffic awareness research in the city of Pekanbaru using qualitative methods based on ticketing data and interviews using the diffusion of innovation theory which focuses on changing ordinary traffic tickets with E-TilangTilang/Tickets given to violators/motorists as sanctions for violations committed.Number of traffic violators in in 2018 there were 13,566 cases of violators and there will be a decrease in 2023, namely 8408 violators, which indicates that E-Tilang helps in reducing traffic violators in the city of Pekanbaru.